2001
DOI: 10.1111/j.1574-6968.2001.tb10861.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the bacterial community to mercury contamination

Abstract: The utilisation of 31 sole carbon sources by bacterial communities of soil in the presence of increasing concentrations of Hg(II) was measured by a colour development assay. The assay was performed on Biolog microtitre plates (Ecoplates) in the presence of Hg(II) and compared to Hg(II)-free Ecoplates. Furthermore, community tolerance to Hg(II) was measured by colour development in microtitre plates supplemented with LB broth and by enumeration of colony-forming units on LB agar plates. Both microtitre plates s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
5
15
0
Order By: Relevance
“…It has been shown that long-term exposure to Cd (months to years) may cultivate a more tolerant community [26], [27], exhibiting enhanced enzyme activities [56]. However, our data indicate that the acclimatisation of the communities to Cd may be achieved after only a few days, which has also been shown in communities exposed to mercury [6]. The low percentage of dead cells in Cd-treated soils also supports this observation.…”
Section: Discussionsupporting
confidence: 79%
“…It has been shown that long-term exposure to Cd (months to years) may cultivate a more tolerant community [26], [27], exhibiting enhanced enzyme activities [56]. However, our data indicate that the acclimatisation of the communities to Cd may be achieved after only a few days, which has also been shown in communities exposed to mercury [6]. The low percentage of dead cells in Cd-treated soils also supports this observation.…”
Section: Discussionsupporting
confidence: 79%
“…Some microbes are capable of using pesticides as a source of energy and may occupy the vacant ecological niche left by the pesticide-sensitive bacteria [23]–[25]. In fact, an increase in the resistant portion of the microbial community is a commonly reported effect of chemical contaminants in aquatic environments [16], [17], [26], [27]. These microbes can mask the effect of pesticides on microbial communities by compensating for microbial biomass, bacterial activity and respiratory deficits associated with loss of pesticide-sensitive microbes [17], [28], [29].…”
Section: Discussionmentioning
confidence: 99%
“…The community‐level physiological profile (CLPP) of the soil microbial populations was determined using BIOLOG EcoPlates ™ (BIOLOG, Hayward, CA, USA) containing 31 different compounds as sole carbon sources. Each plate well was inoculated (150 µl) with a 10 −3 dilution from the microbial enumeration procedure described above 37. Plates were incubated at 27 °C without shaking.…”
Section: Methodsmentioning
confidence: 99%